2017
DOI: 10.1126/scitranslmed.aag2809
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological rescue of diabetic skeletal stem cell niches

Abstract: Diabetes mellitus (DM) is a metabolic disease frequently associated with impaired bone healing. Despite its increasing prevalence worldwide, the molecular etiology of DM-linked skeletal complications remains poorly defined. Using advanced stem cell characterization techniques, we analyzed intrinsic and extrinsic determinants of mouse skeletal stem cell (mSSC) function to identify specific mSSC niche-related abnormalities that could impair skeletal repair in diabetic (Db) mice. We discovered that high serum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 42 publications
4
76
0
Order By: Relevance
“…In the absence of BMP‐2, Sca‐1 + MPCs formed isolated bone nodules and homed to the endosteum (Figure and Figure S2, Supporting Information) comparable to CD146 + human MPCs . These data strongly suggest that trapped Sca‐1 + MPCs contain bone healing‐associated stem and progenitor populations similar to fracture callus‐derived SSCs and could be used to study novel bone healing approaches, including their mobilization to the site of regeneration.…”
Section: Discussionmentioning
confidence: 73%
“…In the absence of BMP‐2, Sca‐1 + MPCs formed isolated bone nodules and homed to the endosteum (Figure and Figure S2, Supporting Information) comparable to CD146 + human MPCs . These data strongly suggest that trapped Sca‐1 + MPCs contain bone healing‐associated stem and progenitor populations similar to fracture callus‐derived SSCs and could be used to study novel bone healing approaches, including their mobilization to the site of regeneration.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, given the tremendous medical burden imposed by degenerative, neoplastic, post-traumatic and post-surgical skeletal disorders, we believe that identifying the hSSC and elucidating its lineage map will enable the molecular diagnosis and treatment of skeletal diseases (Beyth et al, 2011). Using this approach, we recently showed that even complex skeletal pathologies that arise from systemic diseases like diabetes can be precisely diagnosed and remedied by comparing the molecular phenotype of normal and diseased SSCs (Tevlin et al, 2017). Therefore, we anticipate that further characterization of the hSSC, and the ontogeny of hSSC-derived skeletal progenitors as described here will facilitate the development of patient-specific approaches to diagnosing and reversing diverse types of skeletal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has focused on direct application of pharmacologic interventions at the fracture site to increase healing. 28,48 A recent study demonstrated that direct application of SAG, a small molecule Hh pathway agonist, was shown to enhance callus formation in a mouse tibial osteotomy model. 28 However, there are significant clinical drawbacks to therapeutics that require direct administration.…”
Section: Discussionmentioning
confidence: 99%